Exploring Gumuruh Village's Upcycling Potential Using Creative Innovation To Turn Plastic Waste Into Commercial Products - Amalia, Friska; Simarmata, Andriano; Suliastuti, Iftika; Azis, Baskoro; Sabiella, Imanda Dea (Bina Nusantara University, 2024)
Plastic waste presents a major environmental challenge worldwide, with improper disposal endangering ecosystems. Upcycling offers a solution by conserving natural resources, reducing carbon emissions, and minimizing waste, all while lowering the demand for new production. Additionally, recycling generates significant economic benefits, particularly by producing high-quality commercial products in sectors like furniture. In Gumuruh Village, Bandung, the community actively participates in recycling efforts, including the processing of organic waste, to create sustainable products. Through the Design Thinking approach and Service Learning, academics and local SMEs collaborate to design and develop products that directly benefit the community.